2020
DOI: 10.5194/bg-17-6457-2020
|View full text |Cite
|
Sign up to set email alerts
|

Vertical mobility of pyrogenic organic matter in soils: a column experiment

Abstract: Abstract. Pyrogenic organic matter (PyOM) is a major and persistent component of soil organic matter, but its mobility and cycling in soils is largely unknown. We conducted a column experiment with a topsoil and subsoil of a sand and a sandy loam to study the mobility of highly 13C labeled ryegrass PyOM (>2.8 at. %), applied as a layer on a 7 cm long soil column, under saturated conditions. Further, we used fresh and oxidized PyOM (accelerated aging with H2O2) to identify changes in its migration through th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 89 publications
1
6
0
Order By: Relevance
“…-In a recent soil column experiment with a soil similar to that in our study, Schiedung et al (2020) showed that only 1 % of the biochar was lost by leaching, most of it during the first flushing of the column. However, we have soil respiration measurements for the first 3 years, and these measurements confirm the hypothesis that the decrease in biochar during that period was due to microbial activity.…”
Section: Long-term Biochar Degradation and Priming Effect On Somsupporting
confidence: 63%
“…-In a recent soil column experiment with a soil similar to that in our study, Schiedung et al (2020) showed that only 1 % of the biochar was lost by leaching, most of it during the first flushing of the column. However, we have soil respiration measurements for the first 3 years, and these measurements confirm the hypothesis that the decrease in biochar during that period was due to microbial activity.…”
Section: Long-term Biochar Degradation and Priming Effect On Somsupporting
confidence: 63%
“…The challenge arises from the limited understanding of the origin of long-term SOC persistence (Schmidt et al, 2011). Persistence is expected to depend on three major processes (Sollins et al, 1996): (i) physical protection (Balesdent et al, 2000), (ii) physico-chemical protection (von Lützow et al, 2006) and (iii) chemical recalcitrance (Angst et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…(iii) Organic matter chemistry controls the chemical energy available for soil heterotrophic microorganisms, which can result in different rates of decomposition (Manzoni et al, 2010). Even if chemical recalcitrance is regarded as a secondary parameter to explain bulk SOC persistence (Amelung et al, 2008), it could be a relevant parameter for a specific form of SOC: pyrogenic organic carbon (PyOC; Schmidt et al, 2011). Also referred to as black carbon, charcoal or fire-derived OM, it is ubiquitous in soils, representing ca.…”
Section: Introductionmentioning
confidence: 99%
“…In comparison, inputs of C derived from non-pyrolyzed OM litter into soils, such as grass OM in our study, are transported vertically as dissolved organic C (Kalbitz et al, 2000;Kaiser and Kalbitz, 2012). Batch experiments , saturated column experiments (Hilscher and Knicker, 2011b;Schiedung et al, 2020) and field experiments (Major et al, 2010;Maestrini et al, 2014) showed that the transport of PyOM in dissolved and colloidal form represents only <1% of the total PyOM. This transport mainly occurs with the first flush, mobilizing initially soluble PyOM fractions or occurring with aging of the PyOM.…”
Section: Mobility and Translocation Of Pyom And Grass Ommentioning
confidence: 62%
“…The cycling of PyOM in soil can enhance or reduce native SOC decomposition (priming effect), which may affect the total soil C balances (Abiven and Andreoli, 2011;Maestrini et al, 2015;Pluchon et al, 2016). Further, PyOM can have a physico-chemical effect on the native SOC cycling by enhancing its desorption from mineral surfaces due to a higher sorption affinity and thus release more degradable and already sorbed OM from soils (Kaiser and Guggenberger, 2000;Schiedung et al, 2020). We found large spatial variability between our treatment soil cores installed in close vicinity (i.e.…”
Section: Loss Of Fresh Pyom and Om And Related Controlling Factorsmentioning
confidence: 90%